THE ROLE OF PARENTS IN SHAPING CHILDREN'S MORALITY IN KEMBANGAN VILLAGE BAKI SUKOHARJO - Syamsudin Nawwar Hibatulloh; Mohamad Ali (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2023)
Parents play an important role in forming morals in children. However, busy parents are the main reason why parents do not have enough time to educate their children's morals , so that school becomes the child's main education . The formation of morals from childhood is a key factor in developing good morals in children. The aim of this research is to describe the role of parents in shaping children's morals in Dukuh Kembangan Baki Sukoharjo. The method used in this research is descriptive qualitative. Data collection was carried out by observation, interviews and documents, then analyzed by data reduction, data presentation and drawing conclusions. The research results show that the role of parents in shaping children's good morals can play many roles, including: The role of parents is as role models, as educators, and as supervisors. Because this work is very important in forming children's morals. In the role of parents, of course there are supporting and inhibiting factors. Supporting factors include personality, family atmosphere at home, positive environment, and parental attention. Inhibiting factors include lack of knowledge, environment and little time with children. So parents play an important role in forming morals in children, because parents who can educate their children to become individuals with good morals can be said to be successful in educating and forming morals in children.